Renewable night cooled chill water source for energy efficient indoor radiant cooling - Imran, Muhammad Syukri; Baharun, Azhaili; Siti Halipah, Ibrahim; Wan Azlan, Bin Wan Zainal Abidin (Trans Tech Publications Ltd, 2016)
This study investigates cooling of water at night in Malaysian climate as renewable cooling medium source for radiant cooling purpose. An experiment with a 1.95 m2 steel roof rig structure was constructed and night cooling cycle was conducted during the hot season and cold season of the year. Regression model was developed to predict water temperature after the night cooling process and the corresponding water and roof ratio was established. An annual simulation of a low income home model retrofitted with radiant cooling system charged by night cooled water as cooling medium shows that 99% of the time the thermal condition could meet ISO 7730 category C Predicted Mean Vote (PMV) between -0.7 and + 0.7. For an outdoor American Society of Heating, Refrigeration and Air Conditioning Engineers (ASHRAE) design day condition, the peak indoor operative temperature of 37°C could be lowered to about 30°C with the use of radiant cooling system. The calculated energy saving for the home model was 85% or about 15% of the conventional air system operating cost